The Relationship Between Self-Efficacy and Peer Support in Academic Procrastination Behavior - Handayani, Erny Tri; Puji Sugiharto, Dwi Yuwono; Sugiyo, Sugiyo (Universitas Negeri Semarang, 2021)
During learning students are required to be able to complete academic assignments, but the phenomenon that occurs is that many students are late in collecting assignments which later can decline their performance. This research aimed to analyze the relationship between self-efficacy and peer support in academic procrastination behaviour of Public Vocational High School students in Pemalang Regency. The research method used was quantitative. The subjects in this research were students at Public Vocational School in Pemalang Regency in grades X, XI, and XII totalling 1,902 students selected using quota random sampling technique using the General Self-Efficacy Scale (GSE), Academic Procrastination Scale (APS) and Peer Support Scale. The results showed that self-efficacy was negatively related to academic procrastination behaviour, while peer support was negatively related to procrastination behaviour. Finally, self-efficacy and peer support are simultaneously negative to academic procrastination behaviour. At last, this research recommends efforts to reduce procrastination through self-efficacy and peer support.